Study of thulium-167 cyclotron production: a potential medically-relevant radionuclide - Renaldin, Edoardo; Dellepiane, Gaia; Braccini, Saverio; Sommerhalder, Alexander; Zhang, Hui; van der Meulen, Nicholas P.; Eichler, Robert; Talip, Zeynep (Frontiers in Chemistry, 2023)
Targeted Radionuclide Therapy is used for the treatment of tumors in nuclear medicine, while sparing healthy tissues. Its application to cancer treatment is expanding. In particular, Augerelectron emitters potentially exhibit high efficacy in treating either small metastases or single tumor cells due to their short range in tissue. The aim of this paper is to study the feasibility of a large-scale production of thulium-167, an Auger-electron emitter radionuclide, in view of eventual systematic preclinical studies. Proton-irradiated enriched erbium-167 and erbium-168 oxides were used to measure the production cross sections of thulium-165, thulium-166, thulium-167, and thulium-168 utilizing an 18-MeV medical cyclotron equipped with a Beam Transport Line (BTL) at the Bern medical cyclotron laboratory. The comparison between the experimental and the TENDL 2021 theoretical cross-section results were in good agreement. Additional experiments were performed to assess the production yields of thulium radioisotopes in the BTL. Thulium-167 production yield was also measured irradiating five different target materials ( 167) with proton beams up to 63 MeV at the Injector II cyclotron of Paul Scherrer Institute. Our experiments showed that an 8-hour irradiation of enriched ytterbium-171 oxide produced about 420 MBq of thulium-167 with a radionuclidic purity of 99.95 % after 5 days of cooling time with a proton beam of about 53 MeV. Larger activities of thulium-167 can be achieved using enriched erbium-168 oxide with a 23-MeV proton beam, obtaining about 1 GBq after 8-hour irradiation with a radionuclidic purity of <99.5 % 5 days post end of bombardment.